(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
The objective of this work is to investigate the main solar cooling systems, namely photovoltaic (PV) and thermal sorption (absorption and adsorption) systems, in order to identify the most cost-effective technology according to operating and climatic conditions. A technicoeconomic and environmental comparison has been carried out through a case study. The results revealed that the conventional system powered by photovoltaic panels represents the most appropriate choice in terms of annual cold production and levelized cost of energy (LCOE) when compared with the adsorption and absorption systems, but in terms of environmental aspect the choice of the latter systems is more judicious.